Record and provenance of Pleistocene volcaniclastic turbidites from the central Lesser Antilles (IODP Expedition 340, Site U1398B) - Breitkreuz, Christoph; Schmitt, Axel Karl; Repstock, A.; Krause, J.; Schulz, B.; Bergmann, F.; Bischoff, J.; Le Friant, A.; Ishizuka, O. (Marine geology, 2021)
Pleistocene volcaniclastic turbidites drilled during IODP 340 (U1398B, ≤ 170 mbsf) in the Grenada basin west of Martinique (central Lesser Antilles) have been investigated for sediment provenance. U/Pb ages by ion microprobe from 323 detrital zircon grains at three U1398B levels reveal youngest population maximum ages which are interpreted to represent major eruption periods. Systematic age progression with depth defines a ~ 20 cm/ka depositional rate and provides a robust chronostratigraphic frame for the ≤167.5 mbsf (≤ 856 ± 10 ka) interval of U1398B, and confirms on-board paleomagnetic constraints for a possible late Matuyama age for the lowermost sampled parts of U1398B. The achieved chronostratigraphic frame yields sedimentation rates for carbonate ooze and of volcaniclastic sands and gravels of 8.2 and 7.6 cm/ky, respectively. Depth plots of cumulative thickness of these lithologies allow for a differentiation into periods of enhanced and reduced volcanic activity. Porphyritic lava and mineral fragments include plagioclase, diopside, augite and enstatite, as well as magnesio-hornblende and ferri-tschermakite. Geothermobarometry based on clinopyroxene and amphibole reveal the dominant role of upper crustal magma reservoirs. Ferri-tschermakite from 93 and 167.5 mbsf (~410 and 856 ka, respectively) records contributions from lower crustal, hot magma reservoirs. These temperature estimates are supported by Ti-in-zircon data. O-isotope ratios and trace elements in zircon reflect magmatic activity typical for an evolved island arc system. The bathymetry of the Grenada basin, the composition of lava clasts and minerals, scarcity of altered lava fragments, the narrow maximum age population of detrital zircon, and the O-isotope and trace element data on zircon suggest that the majority of U1398B volcaniclastic turbidites originated from the island of Dominica. The thick volcaniclastic units are most likely related to major eruption periods of andesitic magma that ascended from crustal reservoirs. Debris avalanche-related processes seem to be less important in U1398B at ≤170 mbsf. Mineral chemistry and O-isotope data obtained from plagioclase, pyroxene, amphibole, zircon and glass, separated from deep marine volcaniclastic turbidites, provide a chronostratigraphic frame for the sedimentary succession, and helps to genetically fingerprint the volcanic and magmatic evolution of the neighboring volcanic islands. While this is documented here for the well-constrained Pleistocene history of the central Lesser Antilles, the applied methods may also be used to characterize ancient marine volcaniclastic mass flow deposits and to reconstruct their volcanic source areas.
Gesehen am 20.10.2021